Johnson's new handy manual on plumbing, domestic and sanitary engineering, drainage and sewerage - Johnson, John W. (Illinois : [publisher not identified], 1890)
The information contained herein is thoroughly practical and based on the experience of hundreds of the best-known Plumbers, Inspectors, and from City and state codes throughout the country.
Keywords: SANITARY ENGINEERING -- MANUAL